A defense of a weak linguistic relativist thesis. (November 2022) - Colomina-Almiñana, Juan J.
Abstract: By confronting two linguistic myths, a strong linguistic relativist thesis and the idea that communication is the only means of language, this article demonstrates that some aspects of language mold some habits of thought and that language provides different speech communities with distinct behavioral patterns to accomplish specific social actions adequately. The article, thus, argues that there is strong empirical evidence to support a reciprocally influential relationship between language, thought, and society. Highlights: Novel approach to linguistic relativity and conceptual pluralism. It critically analyzes the Sapir-Whorf Hypothesis' origin. It presents an alternative to explicate the interaction between language, thought, and society. It defends empirical evidence that grounds that some aspects of language mold some aspects of cognition.